2020
DOI: 10.3390/genes11091099
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms of TLR4 and TLR9 and Haemophilus influenzae Meningitis in Angolan Children

Abstract: Bacterial meningitis (BM) is a severe disease caused by various bacterial pathogens. Toll-like receptors (TLRs) protect humans from invading pathogens. In this study, we determined whether single nucleotide polymorphisms (SNPs) of TLR4 and TLR9 are associated with susceptibility to and outcome of BM in Angolan children. Samples were taken from 241 patients and 265 age-matched ethnic controls. The SNPs TLR4 rs4986790 (896A > G) and TLR9 rs187084 (−1486T > C) were determined by high-resolution melting anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, Native Americans, Native Alaskans, and African Americans that experience higher rates of invasive bacterial infections due to HI and SP, also show an increased prevalence of congenital immunodeficiencies (such as the Common Variable or Severe Combined Immuno-Deficiency). It is not yet clear whether Toll-Like Receptors 2, 4, and 9 polymorphisms may predict both susceptibility and unfavourable course of bacterial meningitis caused by SP or NM [6][7][8][9][10]. It has, however been demonstrated that TLR-triggered cytokine secretion is involved in the pathogenesis of meningococcal disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Native Americans, Native Alaskans, and African Americans that experience higher rates of invasive bacterial infections due to HI and SP, also show an increased prevalence of congenital immunodeficiencies (such as the Common Variable or Severe Combined Immuno-Deficiency). It is not yet clear whether Toll-Like Receptors 2, 4, and 9 polymorphisms may predict both susceptibility and unfavourable course of bacterial meningitis caused by SP or NM [6][7][8][9][10]. It has, however been demonstrated that TLR-triggered cytokine secretion is involved in the pathogenesis of meningococcal disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 133 age‐ and ethnicity‐matched controls were enrolled between 2008 and 2017. Patients and controls are described elsewhere in further detail [16].…”
Section: Methodsmentioning
confidence: 99%
“…CSF was cultured on blood and chocolate agar plates, and bacteria were identified by Gram stain or standard bacteriological phenotypic methods. Detailed information on the laboratory methods were reported elsewhere [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, polymorphisms of TLRs are involved in the susceptibility to infections; in this context, the TLR2 2477G/A polymorphism contributes to an increased risk of pneumococcal meningitis in the Caucasian population [ 138 ]. In Angolan children, the single nucleotide polymorphism TLR4 rs4986790 increases the susceptibility to bacterial meningitis caused by Haemophilus influenzae, the risk of ataxia, and neurological sequelae, while TLR9 rs187084 decreases the risk [ 139 ]. A meta-analysis revealed that the TLR9 polymorphism rs352140 is associated with a decreased risk of bacterial meningitis [ 140 ].…”
Section: Involvement Of Tlrs In Neuroinflammation and Neurodegenerationmentioning
confidence: 99%